Canon PowerShot G12 : from snapshots to great shots - Carlson, Jeff (Peachpit Press, 2011)
This book is for anyone who wants to get the best shots possible but isn't sure what to do next. There's the manual, as well as competing books, and while they all tell camera owners, often in 400+ pages, what the camera can do, none of them shows them exactly how to use their camera to create great images! Everything in the book is in service of creating a great image. The author carefully guides readers through the modes of the camera and gives practical advice from a pro on which settings to use when, shooting tips, and even end-of-chapter assignments so readers can test their knowledge. Starting with the top ten things users needed to know about the camera, author Jeff Carlson carefully guides readers through the operating features. Owners get practical advice from a pro on which settings to use when, great shooting tips, and even end of chapter assignments.